Work-Life Balance Impact on Gig Workers’ Effectiveness: Moderated of Commitment and Well-Being - Wahyu Maulana; Adriani Kusuma; Moh. Herman Djaja (Universitas Multimedia Nusantara, 2026)
Although WLB has been widely recognized as an important determinant of employee performance, previous studies have reported inconsistent findings regarding its influence on work effectiveness, particularly in the gig economy. Existing research has predominantly emphasized work flexibility, economic outcomes or job satisfaction, while limited attention has been given to explaining whether work commitment and employee well-being strengthen the relationship between WLB and work effectiveness. This theoretical gap remains particularly evident in Indonesia's digital labor sector, where algorithm-driven work systems and flexible employment arrangements create unique challenges for balancing professional and personal life. Therefore, this study investigates the effect of WLB on employee work effectiveness and examines the moderating roles of work commitment and employee well-being among gig workers. This research employed a quantitative associative approach involving JASKU courier employees in Pamekasan, Indonesia. From a population of approximately 125 employees, 95 respondents were selected using probability sampling based on the Slovin formula with a 5% error margin. Data were collected through observation, interviews, and structured questionnaires and analyzed using SEM-PLS with SmartPLS. The findings reveal that work-life balance has a positive and significant effect on work effectiveness (p<0.05). However, work commitment and employee well-being do not significantly moderate this relationship, with significance values of 0.372 and 0.191, respectively (p>0.05). These findings indicate that WLB directly enhances employee work effectiveness regardless of employees' commitment and well-being levels. This study contributes to the WLB literature by addressing an underexplored research gap in the gig economy context and provides practical insights for digital platform companies to strengthen WLB policies that support sustainable employee performance and organizational effectiveness.